2020
DOI: 10.21203/rs.2.12137/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of the comprehensive geriatric assessment on treatment decision in geriatric oncology.

Abstract: Background: The comprehensive geriatric assessment (CGA) is the gold standard in geriatric oncology to identify patients at high risk of adverse outcomes and optimize cancer and overall management. Many studies have demonstrated that CGA could modify oncologic treatment decision. However, there is little knowledge on which domains of the CGA are associated with this change. Moreover, the impact of frailty and physical performance on change in cancer treatment plan has been rarely assessed.Methods: This is a cr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Previous studies have compared the patient characteristics of those with and without a change in treatment decision after a geriatric evaluation. [28][29][30] These studies showed that more impairments in geriatric domains were reported in patients whose treatment decision was modified after evaluation. As pre-frail and frail patients often have multiple geriatric problems, it is high yield to target these patients for a CGA, not only for treatment decision-making, but also for geriatric interventions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have compared the patient characteristics of those with and without a change in treatment decision after a geriatric evaluation. [28][29][30] These studies showed that more impairments in geriatric domains were reported in patients whose treatment decision was modified after evaluation. As pre-frail and frail patients often have multiple geriatric problems, it is high yield to target these patients for a CGA, not only for treatment decision-making, but also for geriatric interventions.…”
Section: Discussionmentioning
confidence: 99%
“…We showed that treatment decisions were more frequently altered in patients who were pre‐frail and frail as compared with fit patients. Previous studies have compared the patient characteristics of those with and without a change in treatment decision after a geriatric evaluation 28–30 . These studies showed that more impairments in geriatric domains were reported in patients whose treatment decision was modified after evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Individual risk factors for NGCaS and NGCaS by number of positive risk factors have to be validated in prospective studies with a large number of patients. Second, the analysis of risk factors for NGCaS after gastrectomy used factors from preoperative examinations usually performed before gastrectomy, such as past history, blood tests, and imaging studies, but did not include items from the detailed functional assessment of elderly patients, such as a comprehensive geriatric assessment 33–35 . Third, in this study, we cannot determine whether the patients who were found to be at high risk for non‐gastric‐cancer‐related death were originally a group of patients with a short life expectancy or whether the surgery had a negative impact on their prognosis.…”
Section: Discussionmentioning
confidence: 98%
“…[29][30][31] This indicates that it is difficult to predict the postoperative life expectancy of postoperative gastric cancer and imaging studies, but did not include items from the detailed functional assessment of elderly patients, such as a comprehensive geriatric assessment. [33][34][35] Third, in this study, we cannot determine whether the patients who were found to be at high risk for non-gastric-cancerrelated death were originally a group of patients with a short life expectancy or whether the surgery had a negative impact on their prognosis.…”
Section: Ta B L E 6 Multivariate Analyses Formentioning
confidence: 92%
“…A current review of CGA showed that there is very great variation regarding which domains are used in CGA and which specific methods are used in each domain [23]. CGA is often carried out using rating scales in various domains [24]. Another proposal is a standardised multidimensional geriatric assessment, based on a menu of rating scales, summarised in a collective risk score for negative health outcomes [25].…”
Section: Treatmentmentioning
confidence: 99%